(untitled) (Journal of Medicine, 2026)
Hypertension has become the leading modifiable risk factor for global deaths. Unlike many sudden illnesses, its progression is usually silent, with vascular damage building over years before leading to stroke, heart attack, heart failure, or chronic kidney disease, earning it the nickname “silent killer.” Even blood pressure higher than normal, without reaching hypertension levels or requiring treatment, raises the risk of death from cardiovascular and other diseases. In 2021, global data show that 53% of all cardiovascular deaths, including 58% of stroke deaths and 31% of chronic kidney disease deaths, were linked to high systolic blood pressure. Overall, high blood pressure contributed to 11 million deaths, or 16% of all deaths worldwide, more than any other risk factor. By 2024, about 1.4 billion adults aged 30–79 globally suffer from hypertension. This accounts for 33% of people in this age group and has remained nearly unchanged since 1990, when it was 32%. However, due to population growth and ageing, the number of affected individuals has more than doubled since 1990, from 650 million. Death rates vary greatly among regions: while 8% of all deaths in the African Region are due to high blood pressure, the rate in the Western Pacific Region is much higher at 22%. Slight differences are also seen between sexes, with high blood pressure causing 15% of deaths in men and 18% in women. Regarding age, 11% of all deaths related to high blood pressure occur in people under 70, and 21% among those 70 and older. In 2018, nearly 20 million adults in Bangladesh had hypertension, but only 38% were receiving treatment, and a mere 15% had their blood pressure controlled. In recent decades, Bangladesh has faced many structural and systemic barriers, such as limited access to essential medicines in rural areas, long waits at primary care clinics, high transportation costs, weak patient follow-up systems, and a lack of awareness about hypertension’s risks. Environmental factors like widespread use of solid fuels have also contributed to a significant rise in hypertension, especially among women.